A Pseudo‐One Compartment Model of Phosphorus Kinetics During Hemodialysis: Further Supporting Evidence. Issue 11 (26th May 2017) - Leypoldt, John K.; Agar, Baris U.; Cheung, Alfred K.; Bernardo, Angelito A.
Abstract: A pseudo‐one compartment model has been proposed to describe phosphorus kinetics during hemodialysis and the immediate post‐dialysis period. This model assumes that phosphorus mobilization from tissues is proportional to the difference between the pre‐dialysis serum concentration (a constant) and the instantaneous serum concentration. The current study is exploratory and evaluated the ability of a pseudo‐one compartment model to describe the kinetics of phosphorus during two short hemodialysis treatments separated by a 60‐min inter‐treatment period without dialysis; the latter is the post‐dialysis rebound period for the first short hemodialysis treatment. Serum was collected frequently during both hemodialysis treatments and the inter‐treatment period to assess phosphorus kinetics in 21 chronic hemodialysis patients. Phosphorus mobilization clearance and pre‐dialysis central distribution volume were previously estimated for each patient during the first hemodialysis treatment and the inter‐treatment period. Assuming those kinetic parameters remained constant for each patient, serum phosphorus concentrations during the second treatment were used to estimate the driving force concentration ( C df ) for phosphorus mobilization from tissues during the second treatment. Treatment time (117 ± 14 [mean ± standard deviation] vs. 117 ± 14 min), dialyzer phosphorus clearance (151 ± 25 vs. 140 ± 32 mL/min), and net fluid removal (1.44 ± 0.74 vs. 1.47 ± 0.76 L) were similar during both short hemodialysis treatments. Measured phosphorus concentration at the start of the second hemodialysis treatment (3.3 ± 0.9 mg/dL) was lower ( P  < 0.001) than at the start of the first treatment or C pre (5.4 ± 1.9 mg/dL). Calculated C df was 4.9 ± 2.0 mg/dL, not significantly different from C pre ( P  = 0.12). C df and C pre were correlated ( R  = 0.72, P  < 0.001). The results from this study demonstrate that the driving force concentration for phosphorus mobilization during hemodialysis is constant and not different from that pre‐dialysis, providing further evidence supporting a fundamental assumption of the pseudo‐one compartment model.